MENILAI KINERJA PERUSAHAAN RETAIL TRADE YANG TERDAFTAR DI BURSA EFEK INDONESIA BERBASIS LAPORAN KEUANGAN - Nasyaroeka, John (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2017)
As for this study reached is to know the performance of the company retail trade in BEI. The contribution of the time period in the study to provide information will be the performance of the company retail trade useful for the investors. Methods used in this study is the documentation the research using the data collection to see its financial report. This study tries to identify financial statements by looking at the performance of retailtrade companies through financial ratios of liquidity ratios, solvency ratios, profi tability ratios and activity ratios. The results of this study indicate that the liquidity ratio of financial position of retail trade companies in very good condition. The solvency ratio shows that the ratio of this ratio indicates a decrease caused by the company being fi nanced almost with part of the debt. The provitability ratio that is represented by the ROA indicator shows that the profit margin obtained by the company looks quite good. While the ratio of activity shows that the average company in the retail trade produces good corporate value. However, the results of the resulting sales have not obtained optimal results